STRENGTHENING STRENGTHENING THE ENTREPRENEURIAL POTENTIAL AND FINANCIAL MANAGEMENT OF SILAYUNG COFFEE FARMERS THROUGH SUSTAINABLE STRATEGIES TO ENHANCE LOCAL - Aliman Ali; Aghni Aulia Aziz; Windari Hikmayanti (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study aims to analyze the entrepreneurial potential of Silayung coffee farmers in Karyamukti Village, Garut Regency, with a focus on financial management and coffee-based business practices. Using a qualitative approach involving interviews, observations, and financial document analysis, the study identifies opportunities, challenges, and strategies for coffee-based economic empowerment that can sustainably increase community income. The results show that although farmers possess significant potential in post-harvest processing and the marketing of value-added products, their primary constraint lies in limited financial management skills, including budgeting, cost control, and inadequate financial record-keeping. It is recommended that a comprehensive training program on business financial management be implemented, covering budgeting, tracking fixed and variable costs, and conducting profit and loss analyses. This would support business sustainability and significantly improve farmers' incomes. These findings highlight the importance of integrating financial management into coffee-based business empowerment strategies to enhance local economic competitiveness and long-term sustainability.